Psychometric properties of the recovery experience scale in Peruvian salaried workers - Mamani-Benito, Oscar Javier; Cruz Ordinola, María Celinda; Llacsa Vásquez, Mercedes; Carmona Brenis, Karina Paola; Asenjo Zapata, Cornelia Yajaira; Bernal Marchena, Luisa Paola de los Milagros; Pichen Fernández, Juan; Tito-Betancur, Madona (Archivos de Prevención de Riesgos Laborales, 2023)
Introduction: After facing a health crisis, it is important for workers to develop recovery experiences; therefore, the objective of this study was to analyze the psychometric properties of the recovery experience scale in Peruvian salaried workers. Method: A cross-sectional study of 462 salaried workers of both sexes, between 20 and 66 years of age, from the three regions of Peru, who participated voluntarily. The participants were recruited from companies in the financial, tourism, education, health and telecommunications sectors. The survey instrument was the recovery experience scale, which had been previously validated for Peruvian teachers. The internal structure was analyzed by confirmatory factor analysis, internal consistency with Cronbach’s alpha (?) coefficient and convergent validity through Pearson’s correlation coefficient. Results: The confirmatory factor analysis showed an adequate fit for the original four-factor structure (x2= 141.782, p < 0.001, CFI = 0.981, RMSEA = 0.065 and SRMR = 0.035). The resulting factor loadings were between 0.71 and 0.90 and the internal consistency ? between 0.81 and 0.92. With respect to convergent validity, direct and significant correlations were found between the recovery experience dimensions and the general well-being scale (r= 0.126 to r=0.287). Conclusions: The recovery experience scale demonstrates validity, based on internal structure, reliability and convergent validity, and can be used in the occupational health management of Peruvian salaried workers.